2013
DOI: 10.14221/ajte.2013v38n4.3
|View full text |Cite
|
Sign up to set email alerts
|

Middle Level Mathematics Teachers’ Self-Efficacy Growth through Professional Development: Differences Based on Mathematical Background

Abstract: Profile analyses were used to investigate differences in the selfefficacy growth of teachers with more and less mathematics background as the teachers participated in professional development across two summers. Professional development activities were associated with increases in teachers' self-efficacy; however, without considering mathematics knowledge for teaching, teachers with more math background tended to benefit more than those with less background. Nonetheless, teachers with less math background had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…At times teacher-centred approaches are beneficial to introduce concepts and model capabilities, however, it is critical that student-centred pedagogies are utilised in order for learners of computing to consolidate understanding, transfer their knowledge, develop their creativity, and have opportunities to learn from peers (Bower, 2011;Bower & Hedberg, 2010). It is suggested through continued professional development, teachers could be able to better adapt their computational thinking pedagogies and approaches based on student needs (Stevens et al, 2013).…”
Section: Teaching Computational Thinking and The Challenges Involvedmentioning
confidence: 99%
See 1 more Smart Citation
“…At times teacher-centred approaches are beneficial to introduce concepts and model capabilities, however, it is critical that student-centred pedagogies are utilised in order for learners of computing to consolidate understanding, transfer their knowledge, develop their creativity, and have opportunities to learn from peers (Bower, 2011;Bower & Hedberg, 2010). It is suggested through continued professional development, teachers could be able to better adapt their computational thinking pedagogies and approaches based on student needs (Stevens et al, 2013).…”
Section: Teaching Computational Thinking and The Challenges Involvedmentioning
confidence: 99%
“…Providing teachers with adequate teaching-related resources is critical in order to improve student outcomes (Stevens et al, 2013). Black et al (2013) suggest that creating communities of practice could allow teachers to share the resources and provide each other with ongoing support.…”
Section: Teaching Computational Thinking and The Challenges Involvedmentioning
confidence: 99%
“…Thus, researchers proposed that, like other social-cognitive types of self-efficacy, teachers' self-efficacy is influenced by personal mastery experiences, vicarious experiences (observation of models), social persuasion, and physiological indicators (Schunk, Pintrich, & Meece, 2008;TschannenMoran & Hoy, 2001). Proxies for these sources of teachers' self-efficacy examined in previous research include, but are not limited to, teaching experience, educational background in the subject matter taught, and professional development experiences (Stevens et al, 2013;Swackhamer, Koellner, Basile, & Kimbrough, 2009;Wolters & Daugherty, 2007).…”
Section: Teachers' Educational Beliefsmentioning
confidence: 99%
“…Moreover, some studies have concluded that there is a negative relationship between the educational background of teachers and their educational beliefs (e.g. Isikoglu, Basturk, & Karaca, 2009;Stevens et al, 2013).…”
Section: Teachers' Educational Backgroundmentioning
confidence: 99%
See 1 more Smart Citation